Review of RFID applications in perishable inventory management - Duong, L.; Wood, Lincoln; Wang, X. (2016)
Radio frequency identification (RFID) technology, which enables real time data collection, has been proposed as a promising solution in perishable inventory management. Research shows that RFID technology has many benefits for perishable products; therefore, this chapter presents an overview of RFID technology and its applications to perishable inventory management. The findings provide a comprehensive review and support the managers in evaluating an investment decision to implement RFID and employ RFID in inventory management for perishable products.